The useful moose : a truthful, moose-full tale - Robinson, Fiona, 1965- (New York : Harry N. Abrams, 2004)
A young girl who loves moose is delighted to find them vacationing in her city, and when she and her family invite three young moose to rest at their home, they quickly discover how useful moose can be.
Accelerated Reader AR
Keywords: Moose -- Fiction; Hospitality -- Fiction; Human-animal relationships -- Fiction; Humorous stories